2019
DOI: 10.1016/j.jnoncrysol.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

The structure of near stoichiometric Ge-Ga-Sb-S glasses: A reverse Monte Carlo study

Abstract: The structure of Ge 22 Ga 3 Sb 10 S 65 and Ge 15 Ga 10 Sb 10 S 65 glasses was investigated by neutron diffraction (ND), X-ray diffraction (XRD), and extended X-ray absorption fine structure (EXAFS) measurements at the Ge, Ga and Sb K-edges. Experimental data sets were fitted simultaneously in the framework of the reverse Monte Carlo (RMC) simulation technique. Short range order parameters were determined from the obtained large-scale configurations. It was found that the coordination numbers of Ge, Sb and S ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…[ 26–28 ] Moreover, Ga atom is present in the present quaternary sulfide glasses, which is supposed to be trivalent in its valence state but fourfold coordinated in its local structural environment. [ 29–32 ] Non‐zero electric dipole moment should be involved between the initial and final vibrational states in order for an IR absorption to take place. [ 22 ] As such, the stronger amplitude of the fundamental vibrational absorption in the sulfide glasses seems to result from their enhanced ionicity.…”
Section: Resultsmentioning
confidence: 99%
“…[ 26–28 ] Moreover, Ga atom is present in the present quaternary sulfide glasses, which is supposed to be trivalent in its valence state but fourfold coordinated in its local structural environment. [ 29–32 ] Non‐zero electric dipole moment should be involved between the initial and final vibrational states in order for an IR absorption to take place. [ 22 ] As such, the stronger amplitude of the fundamental vibrational absorption in the sulfide glasses seems to result from their enhanced ionicity.…”
Section: Resultsmentioning
confidence: 99%
“…The broadening is presumably caused by a distortion of the structural units, namely, an increased variation in the chemical bond angles M-S-M and S-M-S, where M = Sb(Ge,Ga), due to structural disturbance caused by the introduction of the Pr 3+ ion into the glass matrix, forming an atypically high-coordination environment around itself. Thus, the coordination number in glass for Sb is typically three [22,23], and for Ge and Ga, it is four [23,24]. However, for the lanthanide ion (Pr 3+ ), it ranges from 6 to 9 according to various sources [13,25,26].…”
Section: Structure and Optical Propertiesmentioning
confidence: 99%
“…The Sb-S distances were found in the glass structure, which are 0.3–0.4 Å longer than the length of the covalent bond. On the basis of which, it was suggested that Sb atoms can have different local environments [ 12 ]. The glass formation region, density, refractive index, thermal expansion coefficient, T g of this ternary system were studied in [ 13 ].…”
Section: Introductionmentioning
confidence: 99%